Development of public service advertisement about environmental cleanliness using after effect based on motion graphic animation - Dandi Rajki Nurpadilah; Amir Hamzah Pohan; Charmiyanti Nurkentjana Aju; Mochamad Sanwasih; Khadijah Khadijah (Privietlab, 2025)
Advertising is one of the most powerful promotional ways to convey a message or promote something, public service advertisements are one type of advertisement that contains a message to be conveyed to the public. Conventional public service advertisements are usually less interesting because they are not very creative so that people who watch are not interested in the advertisement and the content of the message of the public service advertisement is not conveyed. In making this Motion Graphic Animation mutimedia-based public service advertisement, the author uses the literature study method for data collection and the author uses multimedia-based software such as Adobe After Effect and Adobe Illustrator as support in working on this public service advertisement. This research aims to make people more interested in watching public service advertisements and can understand and apply the useful messages in these public service advertisements.